The ocean at the end of the lane - Gaiman, Neil, (William Morrow, 2013)
It began for our narrator forty years ago when the family lodger stole their car and committed suicide in it, stirring up ancient powers best left undisturbed. Dark creatures from beyond the world are on the loose, and it will take everything our narrator has just to stay alive: there is primal horror here, and menace unleashed - within his family and from the forces that have gathered to destroy it. His only defense is three women, on a farm at the end of the lane. The youngest of them claims that her duckpond is ocean. The oldest can remember the Big Bang.